ALTERNATIF DESAIN GAJI POKOK DI TOKO ROTI XYZ SEMARANG - Registha Elsa Budhiawan (Politeknik Ubaya, 2018)
This study aims to find alternative remuneration based Analytical Hierarchy Process to the salaries of employees inXYZ Bakery, Semarang. The method used in this research is quantitative analysis. Data collection techniques used is by interview and questionnaire to 13 employees Bakeries XYZ, Semarang.Based on the theory Elizur in Sukwadi (2014) were used in this study, by evaluating the positions it will provide a level of objectivity in measuring the comparative value of existing positions within an organization and can assign a relative value positions.Research shows that there is a difference between salary received at Bakery XYZ at 13 positions occupying a position with the calculation using the point system, in which 6 of them as the post of General Manager, Human Resources Manager, Production Manager, Finance Manager, part of the Accounting and parts head Shop excess salaries given. For the remaining seven positions such as CO Bakery, Cake CO, CO basahan, Tax section, part of the Purchase Order, Order parts and parts Shop shortage stipends given.